Genomic characterization of ST11-KL25 hypervirulent KPC-2-producing multidrug-resistant Klebsiella pneumoniae from China - Yuting Kang; Chao Xu; Wanting Ma; Qiujie Li; Wei Jia; Pengtao Wang (iScience)
Summary: The global prevalence of ST11 hypervirulent carbapenem-resistant Klebsiella pneumoniae (hv-CRKP) isolates has been increasingly documented, yet genomic characterization of this clone remains insufficiently explored. Here, we report a clinical ST11-KL25 hv-CRKP strain (KP156) that exhibited resistance to multiple antibiotics and demonstrated hypervirulence in a mouse infection model. Whole-genome sequencing revealed that KP156 harbored one virulence plasmid (pKP156-Vir) and two resistance plasmids (pKP156-KPC and pKP156-tetA). The pKP156-Vir contains several virulence factors, including rmpA2 and iucABCD, which are critical contributors to its hypervirulence. The blaKPC-2 and blaCTX-M-65 genes, located within the Tn6296 transposon of pKP156-KPC, along with a multidrug-resistant (MDR) region containing multiple transposons and conjugative elements in pKP156-tetA, are associated with the transfer of resistance genes. Phylogenetic analysis indicates that KP156 shares high homology with other ST11 hv-CRKPs, suggesting potential transmission of this clone. Our study informs the development of genomic surveillance and control strategies for this strain.